POLA PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN HIPERTENSI - Teti Sutriyati Tutoli; Nur Rasdiana; faradilasandi tahala (Indonesian Journal of Pharmaceutical Education, 2021)
Hypertension is an increase in systolic blood pressure of at least 140 mmHg or a diastolic pressure of at least 90 mmHg. This study aimed to determine the use of drugs in outpatient hypertension patients at the PuskesmasTilamuta. The design employed in this study wa a non-analytic descriptive analysis method by calculating the percentage of the amount of 3T, namely the right indication, the right drug, and the right dose in a non-experimental manner with a cross sectional design (cross-sectional) and retrospective data collection. Data were collected through mecical records of outpatient hypertension patiens in the area from January 2020 to Desember 2020. Then, the research subjects who met the inclusion criteria were 92 patients. The results showed that the calcium channel bloker (Amlodipine) class antihypertensives were mostly used at 53%. Based on the results of the study, it was found that some patients were not given anthypertensive drugs with inappropriate  drug percentage (23%), incorrect indications (23%), inapporiate dosage (23%). Therefore, it is concluded that some patients do not comply with the accuracy of the indication, drugs, and the accuracy of dosage, so it is necessary to monitor the administration of antihypertensive drugs.